Eco-Friendly Batteries from Rice Husks and Wood Grain - A. M. Nurjamil; N. A. Wolio; R. N. Laila; S. A. Rohmah; Asep Bayu Dani Nandiyanto; Sri Anggraeni; Tedi Kurniawan (ASEAN Journal of Science and Engineering, 2021)
The purpose of this study was to find out the carbon influence of rice husks and wood grain as electrolyte absorbers on large voltage and battery life. The battery fabrication procedure is as follows: (1) Preparing sixteen used batteries with a 1.5 Volt voltage, (2) Making NaCl solution with percentages of 10, 20, 30, and 40%, (3) Drying rice husks and wood grain until drying, (4) Carbonizing rice husks and wood grain, (5) Smoothing rice husks and carbonated wood grain, (6) Mixing rice husk, wood grain, and electrolyte solution, (7) Remove the contents of the used battery and wash it thoroughly, (8) Insert carbon from rice husks and wood grain. (9) Perform the process of closing the battery with the battery cover, (10) Measuring the battery voltage using an Avometer. This research shows that carbon derived from rice husks and wood grain can generate electrical voltage, but the resulting voltage is still low compared to commercial batteries. In addition, batteries with electrolyte solutions that have a salt percentage of 10% provide the most voltage.